We know the derivative of ex, which is ex.
(ex)' = ex
We can find the derivative of ecsc√x using chain rule.
Find ᵈʸ⁄dₓ, if
y = ecsc√x
Let u = √x.
y = ecscu
Let v = cscu.
y = ev
y = ev ----> y is a function of v
v = cscu ----> v is is a function of u
u = √x ----> u is is a function of x
By chain rule, the derivative of y with respect to x :
Substitute y = ev, v = cscu and u = √x.
Substitute v = cscu.
Substitute u = √x.
Kindly mail your feedback to email@example.com
We always appreciate your feedback.
©All rights reserved. onlinemath4all.com
May 26, 23 12:27 PM
May 21, 23 07:40 PM
May 20, 23 10:53 PM